E-Consumer Privacy Policy on the Online Marketplace System - khitam, Muhammad chusnul; Suisno; Nugroho, Fajar Seto; Rizkiyah, Putri Ainiyatur (Jurnal Independent, 2024)
Abstract How should the protection of privacy and personal data in Indonesia be responsive to anticipate changing trends from the traditional economic era to the digital economic era? Rapidly developing information and communication technology is changing the way people run business and/or carry out transactions. Thus, transactions which are known as "e-transaction", "e-commerce" and "e-business" have emerged. Indonesia is now in the era of the digital economy. This claim is supported by the condition of Indonesian society which makes the internet and cell phones a commodity, and these commodities are used by traders and sellers to signify electronic transactions via the internet network. This requires that the laws governing these activities can follow or even anticipate developments into the Digital Economy Era.